دور الرقمنة الإدارية في تحسين جودة الخدمات العمومية بالمؤسسة الجزائرية - خلو، الجمعي; تدر، عادل (University Of Eloued جامعة الوادي, 2024)
هــدفت دراستنا للتعرف على دور الرقمنـــة الإداريـــــــة في تحسين جودة الخدمات العمومية، دراسة حالة مصلحة التوثيق البيومتري لبلدية تـــوقرت، وقد انطلقت من الإشكالية التالية: هل للرقمنة الإدارية دور في تحسين جودة الخدمات العمومية بمصلحة التوثيق البيومتري لبلدية توقرت؟ وقد أدرجنا تحته الأسئلة الفرعية التاليـــــــــــــــــــــــــــــــــــــــــــــة: هل الرقمنة الإدارية بمصلحة التوثيق البيومتري لبلدية تـــوقرت تؤدي الإستجابة المناسبة للمواطنين ؟ هل الرقمنة الإدارية تؤدي إلى زيادة رضا المواطنين عن الخدمة العمومية بمصلحة التوثيق البيومتري لبلدية تـــوقرت؟ هل الرقمنة الإدارية عملية ملموسة للمواطن في تحسين جودة الخدمات العمومية بمصلحة التوثيق البيومتري لبلدية تــوقرت؟ واعتمدنا في هذه الدراسة على المنهج الوصفي ، و تم الاعتماد على العينة العشوائية البسيطة نظرا لطبيعة الموضوع المدروس، كما تم استخدام أداة الاستبيان لجمع المعطيات ،وكذا الوثائق الإدارية (المراسيم- برقيات-إرساليات) وقد خلصنا في دراستنا إلى النتائج التالية: - وجود وسائل وتجهيزات للإدارة الرقمية ذات مستوى عالي بمصلحة التوثيق البيومتري لبلدية توقرت. - وجود سجل الملاحظات والإقترحات للمواطنين بمصلحة التوثيق البيومتري لبدية توقرت. - وجود برقيات ومراسيم وقوانين صادرة عن السلطة العليا بخصوص استخدام الرقمنة وكذا تحسين الخدمة العمومية للمواطن. - وجود إقبال من طرف المواطنين بمصلحة التوثيق البيومتري لبلدية توقرت للحصول على الوثائق البيومترية Our study aimed to identify the role of administrative digitization in improving the quality of public services, a case study of the Biometric Documentation Service of the Municipality of Touggourt, and it was based on the following problem: Does administrative digitization have a role in improving the quality of public services at the Biometric Documentation Service of the Municipality of Touggourt? We have included the following sub-questions under it: Does administrative digitization at the Biometric Documentation Service of the Municipality of Touggourt lead to an appropriate response to citizens? Does administrative digitization lead to increased citizen satisfaction with public service at the Biometric Documentation Service of the Municipality of Touggourt? Is administrative digitization a tangible process for the citizen in improving the quality of public services at the Biometric Documentation Service of the Municipality of Touggourt? In this study, we relied on the descriptive approach, and relied on a simple random sample due to the nature of the subject studied, and the questionnaire tool was used to collect data, as well as administrative documents (decrees - telegrams - dispatches). In our study, we concluded the following results: - The presence of high-level digital management tools and equipment at the Biometric Documentation Service of the Municipality of Touggourt. - The presence of a record of observations and suggestions for citizens at the Biometric Documentation Service of the Municipality of Touggourt. - The presence of telegrams, decrees and laws issued by the highest authority regarding the use of digitization and improving public service for citizens. - The presence of citizens' interest in the Biometric Documentation Service of the Municipality of Touggourt to obtain biometric documents
دراســـــــــــــة حالـــــــــة بمصلحة التوثيق البيومتري لبلدية توقـــــــــــرت
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: الرقمنة الإدارية; Administrative digitization; الخدمات العمومية; Public Services